2019
DOI: 10.1186/s12884-019-2573-3
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of antenatal care indicators from self-reported questionnaire and the antenatal care card of women in the 2015 Pelotas birth cohort, Rio Grande do Sul, Brazil

Abstract: BackgroundStudies of healthcare service use during the pregnancy-postpartum cycle often rely on self-reported data. The reliability of self-reported information is often questioned as administrative data or medical records, such as antenatal care cards, are usually preferred. In this study, we measured the agreement of antenatal care indicators from self-reported information and antenatal care cards of pregnant women in the 2015 Pelotas Birth Cohort, Brazil.MethodsIn a sample of 3923 mothers, indicator agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Worth to be noted however is that the Assaf study only focused on the counselling aspect of maternal and child care interventions and did not include the observable components of ANC. In Brazil, Morón-Duarte et al (31) also reported moderate to high agreement on indicators of service utilization, clinical examination and diseases during pregnancy but poor agreement on indicators of counselling. Bessinger and Bertrand (18) conducted a study in Ecuador, Uganda and Zimbabwe to examined the comparability of reports from direct observations and exit interviews at health facilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Worth to be noted however is that the Assaf study only focused on the counselling aspect of maternal and child care interventions and did not include the observable components of ANC. In Brazil, Morón-Duarte et al (31) also reported moderate to high agreement on indicators of service utilization, clinical examination and diseases during pregnancy but poor agreement on indicators of counselling. Bessinger and Bertrand (18) conducted a study in Ecuador, Uganda and Zimbabwe to examined the comparability of reports from direct observations and exit interviews at health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Morón-Duarte et al (31) examined the agreement of antenatal care indicators from self-reported questionnaire and the antenatal care card also reported low reporting accuracy of counselling indicators. On the other hand, a recall study of maternal and newborn interventions received in the postnatal period in Kenya and eSwatini found that some indicators of physical examination had higher reporting accuracy (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In common with other DHS surveys, maternal tetanus vaccination is self-reported and subject to inaccurate recall. However, a previous study from Brazil showed that self-reported uptake of maternal TT vaccination can be higher compared with information in medical records [29]. In addition, ethnicity and religion could be important determinants of maternal vaccination [30].…”
Section: Discussionmentioning
confidence: 99%